Autoconfiança no manejo das intercorrências de saúde na escola entre professores da educação infantil e fundamental I - Zonta, Jaqueline Brosso (2018)
Introduction: school is a favorable environment for health problems. Prevention and health promotion actions are priorities, however, it is necessary for teachers to know how to handle the situation. Yet educators are fearful and insecure. General objective: to analyze the self-confidence of preschool and basic education teachers with regard to the management of health problems at the school. Specific objectives: to describe the construction and validation of the visual analog scale of self-confidence of teachers to handle health problems at school and to identify the factors associated with self-confidence before and after educational activities and associated to the promotion of self-confidence. Method: organized in two stages: the first stage refers to the first specific objective and is characterized as a methodological study. Twelve judges participated in the content validation and 25 teachers in the semantic validation. Internal consistency was determined by Cronbach's alpha coefficient. The second stage addressed the second specific objective and is characterized as a quasi-experimental pre- and post-test study. Seventy-six teachers participated, subdivided into four schools. For each school, the production of the empirical material took place in three meetings. The research instruments used were: characterization tool; Visual analog scale of teachers' self-confidence to manage health problems at school; Knowledge assessment questionnaire to deal with health problems at school and Scale of satisfaction with the simulated clinical experiences. The educational activity consisted of four simulated scenarios. Data were analyzed using descriptive and analytical statistics, using the Mann-Whitney test, Kruskal-Wallis, Spearman's correlation coefficient and multivariate linear regression. The ethical provisions for research involving human beings were met. Results: The final visual analog scale consists of 12 items. All items were evaluated as pertinent, obtaining 100% of agreement among the judges and being considered clear by the target audience, with high internal consistency among the items. Regarding the second stage, a low average self-confidence score was found before the educational activity. After participating in the simulated scenarios, self-confidence was promoted. The variable "background experience with health problems" presented a statistically significant association with the mean self-confidence score (p=0.026) and the mean self-confidence promotion score (p=0.001). The variable "knowledge promotion" had a weak negative correlation with the mean self-confidence score (p=-0.273). The variable "professional experience" maintained a significant relationship with the mean self-confidence score in the post-phase (p=0.008). Final considerations: teachers feel uncomfortable to cope with health problems at school. The results can support the planning of health education actions in the school environment.